HER-2-positive metastatic breast cancer: new possibilities for therapy - E. V. Artamonova; L. V. Manzyuk (Опухоли женской репродуктивной системы, 2014)
This article is devoted to modern approaches in HER-2-positive metastatic breast cancer therapy. Recently treatment algorithm for this type of cancer included trastuzumab plus cytostatic in first line, continuation of trastuzumab with another chemotherapy regimen in second line, further switch to lapatinib and eventual return to trastuzumab after progression. Nowadays our options are broader owing to new anti-HER-2 agents which are pertruzumab and T-DM1. Now the most effective therapy regimen in first line is double HER-2 blockade (trastuzumab + pertuzumab) in combination with docetaxel. Benefit of new agent T-DM1 versus combination of lapatinib and capecitabin is proved in patients progressed on trastuzumab and taxanes. T-DM1 also showed high efficacy as salvage therapy in intensively pretreated patients with meta- static HER-2-positive breast cancer who progressed on taxanes, trastuzumab and lapatinib.